2007
DOI: 10.4321/s0365-66912007000600005
|View full text |Cite
|
Sign up to set email alerts
|

Distribución por edades del melanoma de úvea y su relación con la supervivencia

Abstract: Uveal melanoma in Spain has a similar age distribution to that of other countries, and it is not an infrequent diagnosis in patients under 40 years of age. Survival rates are also similar to that of other series. We have not found any significant difference between the age of our patients and the survival, although if we analysed the subgroups, we found that the men equal to or over 50 years of age had a better survival than the women of the same age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…These results are similar to large retrospective studies by Graell et al and Damato and Damato who reported a mean age of 60.1 and 62.1 years for UM patients, respectively, and Anastassiou et al and Kimura et al who reported a mean age of 60 and 62.3 years for CM patients, respectively 7,20–22. McLaughlin et al conducted a large population-based retrospective study including 4,885 OM patients and reported that the incidence of OM was 8–10 times higher among Caucasians compared to African Americans 2.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are similar to large retrospective studies by Graell et al and Damato and Damato who reported a mean age of 60.1 and 62.1 years for UM patients, respectively, and Anastassiou et al and Kimura et al who reported a mean age of 60 and 62.3 years for CM patients, respectively 7,20–22. McLaughlin et al conducted a large population-based retrospective study including 4,885 OM patients and reported that the incidence of OM was 8–10 times higher among Caucasians compared to African Americans 2.…”
Section: Discussionsupporting
confidence: 91%
“…Singh et al studied 4,070 UM patients and noted that 51.8% of patients were males 4. In contrast, Graell et al noted that 55.8% of their 303 UM patients were females, while Yu et al reported that 41% of their 206 CM patients were females 18,20. A higher incidence in females (55%) was also reported in a study of 194 Dutch CM patients 14.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding demographic data, no significant differences were found in terms of sex and laterality of the pathological eye; however, the mean age of patients diagnosed with uveal melanoma in the period 2020−2021 was lower than the previous year (60.95 SD 14.82; p < 0.05), following a distribution similar to other series described. 13 …”
Section: Discussionmentioning
confidence: 99%
“…27  Factores epidemiológicos: Se han publicado varios trabajos que muestran un peor pronóstico de la mujer frente al hombre 28 y la ausencia de relevancia de la edad en el momento del diagnóstico del melanoma uveal. 29 Los estudios de la supervivencia en el melanoma uveal comienzan de la mano de Zimmerman en EEUU 20 En 1992, Diener-West 3 publico un metaanálisis resumiendo todos los trabajos publicados en materia de supervivencia entre 1966-1988. Observó que la mortalidad a los 5 años post-enucleación para tumores pequeños, medianos y grandes era del 16%, 32% y 52% respectivamente.…”
Section: Justificación Y Propósito Del Estudiounclassified